A Rare Case of Primary Endometrial Hepatoid Adenocarcinoma on 18F-FDG PET/CT. (July 2019) - Yin, Hongyan; Hu, Yan; Xiu, Yan; Luo, Rongkui; Shi, Hongcheng
Abstract : Abstract: Primary endometrial hepatoid adenocarcinoma is a rare tumor. We present a case of a 64-year-old woman with vaginal bleeding for 2 months and a markedly elevated serum α-fetoprotein of 3931 ng/mL. Hysteroscopic segmental curettage revealed endometrial adenocarcinoma. A pelvic MRI was performed for local tumor invasion, which showed only endometrial mass. An abdominal enhanced CT showed no liver lesion, which excluded primary hepatic carcinoma. Staging 18 F-FDG PET/CT demonstrated a hypermetabolic mass in the endometrium. A total hysterectomy with bilateral salpingo-oophorectomy and regional lymphadenectomy were performed. Postoperatively, the mass was diagnosed as primary endometrial hepatoid adenocarcinoma.